2006
DOI: 10.1002/eji.200526208
|View full text |Cite
|
Sign up to set email alerts
|

Migration of cytotoxic T lymphocytes toward melanoma cells in three‐dimensional organotypic culture is dependent on CCL2 and CCR4

Abstract: Studies in experimental animal models have demonstrated that chemokines produced by tumor cells attract chemokine receptor-positive T lymphocytes into the tumor area. However, in cancer patients, the role of chemokines in T lymphocyte trafficking toward human tumor cells is relatively unexplored. In the present study, the migration of a melanoma patient's CTL toward autologous tumor cells has been studied in a novel three-dimensional organotypic melanoma culture. In this model, CTL migrated toward tumor cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 39 publications
4
63
1
Order By: Relevance
“…Recently, Metelitsa et al (40) have shown that 53% of primary neuroblastomas from patients with metastatic disease (stage 4) secrete MCP-1, suggesting that there is heterogeneity of MCP-1 expression even within a certain type of tumor. This may help explain the fact that our studies with the human melanoma A2058 cells are in direct contrast to the recent report by Zhang et al (33), where it was found that human T cell migration toward autologous melanoma cells in culture was dependent on MCP-1/CCL2. Furthermore, our studies do not preclude the necessity of future studies aimed at identifying chemokines other than MCP-1 that mediate T cell tumor tropism, especially because the chemotactic capacity of SW480 cells appeared to be independent of MCP-1 (and IL-8).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Recently, Metelitsa et al (40) have shown that 53% of primary neuroblastomas from patients with metastatic disease (stage 4) secrete MCP-1, suggesting that there is heterogeneity of MCP-1 expression even within a certain type of tumor. This may help explain the fact that our studies with the human melanoma A2058 cells are in direct contrast to the recent report by Zhang et al (33), where it was found that human T cell migration toward autologous melanoma cells in culture was dependent on MCP-1/CCL2. Furthermore, our studies do not preclude the necessity of future studies aimed at identifying chemokines other than MCP-1 that mediate T cell tumor tropism, especially because the chemotactic capacity of SW480 cells appeared to be independent of MCP-1 (and IL-8).…”
Section: Discussioncontrasting
confidence: 83%
“…tumor xenografts in response to the tumor-derived chemokine MCP-1. Although our data suggest that this chemotaxis may be mediated through CCR2, future studies will better define the receptors involved in the observed MCP-1-mediated homing of T cells to tumors, since others have found that MCP-1 directed migration can be dependent on CCR4 (32,33).…”
Section: Discussionmentioning
confidence: 68%
“…Analysis in two different in vitro culture systems showed that migration is dependent on CXCL12 produced by tumor cells and CXCR4 expressed by T cells, consistent with the previous demonstration of chemokine dependency of human CTL migration toward tumor cells. 7,8 The reconstruct culture system which consists of a bottom layer of collagen type I with fibroblasts, superimposed by a tumor cell layer, collagen/fibroblast separating layer and finally a top layer of collagen, fibroblasts and T cells, has several advantages over the Transwell plate cultures usually used to study chemotaxis of T cells: (i) the cultures include growing tumor cells whereas Transwell does not; (ii) chemokines are produced by the growing tumor cells in physiological concentrations as compared to the artificially high chemokine concentrations used in Transwell; (iii) collagen and fibroblasts, missing from Transwell, provide stromal components important for T-cell migration and activation; 29 (iv) T-cell migration can be determined over 6-9 days as compared to a few hours for Transwell; and (v) T cells migrate through a distance of at least 500 µm, as compared to about 10 µm using Transwell. In the reconstruct, human melanoma is recapitulated in vitro using a mixture of collagen and fibroblasts (lattices or matrices).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that migration of CTL derived from two melanoma patients toward autologous tumor cells is dependent on CXCR4 or CCR4 expressed by the CTL and on CXCL12 or CCL2 produced by the melanoma cells. 7,8 Here, we have examined chemokine and chemokine receptor usage for T cell migration in one additional patient and chemokine/chemokine receptor expression in 12 additional melanoma patients, since involvement of the same chemokine in the migration toward autologous melanoma cells of CTL derived from different patients would underscore the potential usefulness of this chemokine in immunotherapy of melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…It allows CTL migration and killing of specific tumor cells and better reflects the cell-to-cell and cellto-matrix interactions occurring in an in vivo tumor microenvironment (19,21). The three-dimensional construct consisted of a collagen matrix containing autologous tumor, endothelial, and CD8 ϩ CTLs.…”
Section: The Lysis Of M4e Ecs By the Tumor-specific Clone Requires Thmentioning
confidence: 99%